Respon Viabilitas dan Pertumbuhan 4 Genotipe Sorgum (Sorghum bicolor [L.] Moench) Pasca Simpan 14 Tahun pada Suhu 50C - Ningsi, Ratna Ningsi; S. Sarungallo, Amelia; Tan, Theresia (Jurnal Ilmu Pertanian dan Perkebunan, 2023)
The research aimed to obtained the viability response of sorghum seeds and their growth after being stored for 14 years at 50C. This study was designed using a randomized block design with 1 factor (genotype). The treatment consisted of 4 genotypes, namely Kawali variety, Numbu variety, S1 line and S4 line. Each treatment was repeated 9 times so that there were 36 experimental units. Each experimental unit consisted of 1 plant. The results of the analysis of variance showed that the percentage of normal germination, the percentage of dead seeds, growth speed, plant height and number of leaves were not affected by genotype. The average percentage of normal germination was 41.71%, the percentage of dead seeds was 58.29%, the growth rate was 12.12%. The average plant height at 5 weeks after planting was 117.55 cm with an average number of leaves was 8.5.